Comparison of minimal inhibitory and bactericidal capacity of oral penicillin V with benzathine penicillin G to Streptococcus beta--hemolyticus group A in children with rheumatic heart disease - Burhanuddin Iskandar; Bambang Madiyono; Sudigdo Sastroasmoro; Sukman T. Putra; Mulyadi M. Djer; Anis Karuniawati (Paediatrica Indonesiana, 2008)
Background Injection ofbenzatine penicillin G (BPG) every 28days is still the drug of choice for secondary prevention of rheu-matic heart disease (RHD). BPG sometimes poses problems dueto pain at the injection site, possible anaphylaxis, and is not alwaysavailable. Some centers choose oral penicillin over BPG.Objectives To compare minimal inhibitory capacity (MIC) andminimal bactericidal capacity (MBC) of oral penicillin V serumwith those of BPG among SGA infected RHD.Methods This was a clinical trial with crossover design study tocompare MIC of penicillin V and BPG. Outcome measures wereMIC and MBC. Statistical analysis was performed using pairedt-test and wilcoxon test.Result There were 32 subjects consisted of 17 males and 15females. The mean value of MIC and MBC serum of penicillinV were 0.031 and 0.125. The mean value of MIC and MBCserum of BPG3 were 0.094 and 0.031. Respectively the MICof penicillin V was similar to that of BPGy The mean value ofMIC and MBC of BPG4 were 0.125 and 0.250. Respectively theMIC of penicillin V was significantly higher than that of BPG 4.The MBC of penicillin V was significantly higher than that ofBPG 4. The MIC ofBPG 3 was similar to that ofBPG 4• The MBCof BPG 3 was similar to that of BPG 4.Conclusions The MIC of penicillin V was similar to that ofBPG 3,the MBC of oral penicillin V was higher than that ofBPG 3• TheMIC and MBC of penicillin V was higher than those of BPG 4.